Determinants of overweight/obesity among Filipino adolescents 2018 expanded national nutrition survey - Platon-Desnacido, Josie; Dasco, Ma. Lilibeth P.; Duante, Charmaine A.; Agdeppa, Imelda Angeles (2022)
The prevalence of overweight and obesity among children and adolescents has been increasing worldwide. In the Philippines, the prevalence of adolescent overweight/obesity showed an increasing trend – from 4.9% in 2003 to 9.2% in 2015 and 11.6% in 2018. Obesity increases the risk of cardiovascular diseases, diabetes, some cancers, and other non-communicable diseases. This study aimed to identify major potential determinants of overweight/obesity among Filipino adolescents from the Food and Nutrition Research Institute’s Expanded National Nutrition Survey (ENNS). Univariate and multivariate analyses of the 2018 ENNS were done and included sociodemographic, socio-economic, clinical, and dietary data as potential determinants of adolescent overweight/obesity. Findings revealed that 12.0% of Filipino adolescents were overweight/obese. The odds of being overweight/obese was 75% (OR: 1.75; CI = 1.42–2.15; p < 0.001) higher with energy intake above requirements and 45% (OR: 1.45; CI = 1.25–1.67; p < 0.001) higher with protein intake above requirement. The risk of becoming overweight/obese in adolescents was higher among 10–12 yr old (OR: 1.61; CI = 1.23–2.10; p = 0.002), from households with less than five members (OR: 1.60; CI = 1.27–2.02; p = 0.001), living in urban areas (OR: 1.30; CI = 1.13–1.51; p = 0.001), from the richest wealth quintile (OR: 3.49; CI = 2.40–5.06; p < 0.001), whose households were food secure (OR 1.46; CI = 1.20–1.79; p = 0.001), and those household heads with at least college level of education (OR 1.56; CI = 1.15–2.13; p = 0.008), and who were physically inactive (OR: 1.41; CI = 1.08–1.84; p = 0.016). The dramatic rise in the prevalence trend of overweight/obesity among Filipino adolescents calls for integrated efforts of both the public and private sectors to focus on policies that would influence the promotion and support of overweight/obesity prevention. These findings may also serve as basis and inputs in modifying eating behaviors and the importance of increasing physical activity targeting the richest quintile in urban areas to help curb the overweight/obesity among adolescents.
Keywords: Obesity; Lifestyles and health